SATIRA AS A FORM OF IMAGE THINKING - Agabey, Gulshen Shahmurad qızı (International Journal of Psychosocial Rehabilitation, 2020)
The article analyzes satire, humor, comedy and their theoretical foundations. It is noted that the functions of satire in the artistic text are multifaceted and therefore, theorists examine it as a literary form, as a genre and as a literary feature. The fundamentals of the polemic associated with the place of satire in artistic thought have been laid since the time of Aristotle. In subsequent periods, Boileau, MF Akhundzadeh, V. Belinsky, B. Zemidok, N. Chernyshevsky, Hegel, G. Pospelov, Yu. Elsberg, A. Abiev, I. Gabibbeyli and others brought clarity to the place occupied by satire and position in artistic thinking. The general meaning of these studies is that satire acts both as a genre, as a kind of literature, and as an artistic feature. Type of Paper— Review